Côtoyer les dieux L'organisation des espaces dans les sanctuaires grecs et romains - Huber, Sandrine; Van Andringa, William (Suppléments du BCH, 2022)
This monograph is the last part of the scientific publication of the programme entitled "Spaces and Rites. The Archaeology of Worship in the Sanctuaries of the Mediterranean World", common to the French Schools at Athens and Rome (2012-2016), and brings together ten essays. Faced with the semantic wealth of literary genres and narrative processes, archaeology provides us with a huge variety of material information that makes absolute sense and covers at least three areas, architecture and the organisation of spaces, iconographical objects and programmes, as well as the practices carried out in sacred spaces, be they ritualistic or not. The main issue here is the place of religion in the everyday life of the cities: the Gods were everywhere, "in spaces with little human presence", inside and outside the walls, in urban spaces, in the private sphere but also, and above all in the wild. Here, researchers that specialise in ancient sanctuaries analyse the way the divine is perceived, in all of its forms.